Pregunta
upstudy study bank question image url

Solve the equation. \[ \frac{2 x-6}{x}=\frac{x-3}{3} \]

Ask by Schwartz Estrada. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

The solutions are \(x=3\) and \(x=6\).

Solución

Solve the equation \( \frac{2x-6}{x}=\frac{x-3}{3} \). Solve the equation by following steps: - step0: Solve for \(x\): \(\frac{2x-6}{x}=\frac{x-3}{3}\) - step1: Find the domain: \(\frac{2x-6}{x}=\frac{x-3}{3},x\neq 0\) - step2: Cross multiply: \(\left(2x-6\right)\times 3=x\left(x-3\right)\) - step3: Simplify the equation: \(3\left(2x-6\right)=x\left(x-3\right)\) - step4: Calculate: \(6x-18=x\left(x-3\right)\) - step5: Calculate: \(6x-18=x^{2}-3x\) - step6: Move the expression to the left side: \(6x-18-\left(x^{2}-3x\right)=0\) - step7: Calculate: \(9x-18-x^{2}=0\) - step8: Factor the expression: \(\left(-6+x\right)\left(3-x\right)=0\) - step9: Separate into possible cases: \(\begin{align}&-6+x=0\\&3-x=0\end{align}\) - step10: Solve the equation: \(\begin{align}&x=6\\&x=3\end{align}\) - step11: Check if the solution is in the defined range: \(\begin{align}&x=6\\&x=3\end{align},x\neq 0\) - step12: Find the intersection: \(\begin{align}&x=6\\&x=3\end{align}\) - step13: Rewrite: \(x_{1}=3,x_{2}=6\) The solutions to the equation \(\frac{2x-6}{x}=\frac{x-3}{3}\) are \(x=3\) and \(x=6\).

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Mind Expander

To solve the equation \[ \frac{2x-6}{x}=\frac{x-3}{3}, \] let's start by cross-multiplying to eliminate the fractions: \[ 3(2x - 6) = x(x - 3). \] Expanding both sides gives: \[ 6x - 18 = x^2 - 3x. \] Rearranging this equation to set it to zero: \[ x^2 - 3x - 6x + 18 = 0 \implies x^2 - 9x + 18 = 0. \] Next, we can factor the quadratic: \[ (x - 3)(x - 6) = 0. \] Setting each factor to zero provides the solutions: \[ x - 3 = 0 \implies x = 3, \] \[ x - 6 = 0 \implies x = 6. \] Now, we should verify if these solutions are valid by substituting them back into the original equation. Both \( x = 3 \) and \( x = 6 \) result in valid equations without leading to division by zero. Thus, the solutions to the equation are: \[ \boxed{3} \quad \text{and} \quad \boxed{6}. \]

preguntas relacionadas

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad